Optimal Portfolio Analysis with Solver Application in Wetland Plantation Subsector - Sadikin, Ali; Fahmi Roy Dalimunthe; Nadia Zulfati Fairuz; Dina Nugraheni (Open Access Indonesia Journal of Social Sciences, 2023)
Investments made by investors should submit to a Markowitz portfolio, where the goal is to get an optimal portfolio investment from several existing stocks. The goal of a portfolio is to maximize stock returns and minimize risk. The object of this study is plantation sub-sector companies listed on the IDX for the 2018-2022 period. The population is 19 companies in the plantation sub-sector, while the sampling method is 6 companies using purposive sampling. Through this research, investors are expected to be able to see which stock portfolio is the most optimal of several efficient portfolios in the agricultural sector. In addition, the plantation sub-sector supports government programs on food security for industry and consumers and increases non-oil and gas income, and increases the income of all relevant stakeholders, which in turn can increase the income and welfare of the Indonesian people.